Where the thread of home births never broke – An interview with Susanne Houd - Santos, M. (Women and Birth, 2017)
Background The option of a planned home birth defies medical and social normativity across countries. In Denmark, despite the dramatic decline in the home birth rates between 1960 and 1980, the right to choose the place of birth was preserved. Little has been produced documenting this process. Aim To present and discuss Susanne Houd's reflection on the history and social dynamics of home birth in Denmark, based in an in-depth interview. Methods This paper is part of wider Short Term Scientific Mission (STSM), in which this interview was framed as oral history. The whole interview transcript is presented, keeping the highest level of detail. Findings In Susanne Houd's testimony, four factors were highlighted as contributing to the decline in the rate of home births from the 1960s to the 1970s: new maternity hospitals; the development of obstetrics as a research-based discipline; the compliance of midwives; and a shift in women's preference, favouring hospital birth. The development of the Danish home birth models was described by Susanne Houd in regard to the processes associated with the medicalisation of childbirth, the role of consumers, and the changing professional dynamics of midwifery. Conclusion An untold history of home birth in Denmark was documented in this testimony. The Danish childbirth hospitalisation process was presented as the result of a complex interaction of factors. Susanne Houd's reflections reveal how the concerted action of consumers and midwives, framed as a system-challenging praxis, was the cornerstone for the sustainability of home birth models in Denmark.